Effects of homozygosity on sex determination in zebrafish Danio rerio. Issue 6 (16th December 2018) - Delomas, Thomas A.; Dabrowski, Konrad
Abstract : Gynogenetic zebrafish Danio rerio were obtained by activating D. rerio oocytes with UV irradiated common carp Cyprinus carpio sperm and then applying one of four different shocks [two (early) meiotic and two (late) mitotic shocks]. Gynogens produced by three of the shocks survived to maturity. All adult gynogens ( n = 52) except one were found to be male. There was no difference in growth rate between the biparental controls and gynogens produced through the most effective shock, thereby eliminating growth rate as a possible cause of the skewed sex ratio. Gynogen males had reduced fertility compared to biparental controls, with about half of gynogens being unable to reproduce through natural spawning (all controls reproduced successfully). Gynogen males that did reproduce gave lower fertilization rates compared with controls. This demonstrates the negative effects of increased homozygosity on male reproductive function. Families sired by meiotic gynogen males were more likely to be female biased (33% of families) compared with families sired by biparental control males (11%). In addition to confirming the polygenic nature of sex determination in D. rerio, these observations suggest that recessive or over‐dominant male‐determining alleles are present in domesticated D. rerio populations.